Emotional aspects of school learning: what do students feel during lectures? - Ćirković-Miladinović, Ivana; Milovanović, Radmila; Stojanović, Biljana (Technium Social Sciences Journal, 2021)
Starting from the point of understanding learning and teaching, which includes considering the role of emotional regulation in educational practice, the main goal of the research was to analyse students’ emotional reactions to lectures and identify possible differences between students’ emotional reactions in Serbia, Hungary and Germany. The sample consisted of 305 students between 14 and 19 years of age from Serbia, Germany and Hungary. The Shabot and Shabot (2009) Questionnaire for self-assessment of emotional reactions in teaching was used to collect data on students’ emotional reactions. The results showed that students in the overall sample respond to lectures with weak and moderate emotional reactions. Statistically highly significant differences (p <0.001) were found in the type and intensity of emotional reactions between students from Serbia and Germany, Serbia and Hungary, as well as Germany and Hungary in almost all emotional modalities. Significant differences (p <0.005) were also found between the sexes and students of different ages in a small number of emotional reactions. The results indicate the importance of encouraging pleasant emotional reactions in teaching and the need to pay more attention to negative emotional reactions. Also, the research shows the need for further research in this area.